PENGARUH SARANA PRASARANA DAN CARA BELAJAR SISWA TERHADAP PRESTASI BELAJAR SISWA - Hera Bianti, ; Naimatul Khusnah, (Pendidikan Ekonomi, 2012)
The goal of this research is to find out the effect of the facilities given and the studying method to the X AP student achievement in SMK Taruna Jaya Gresik. This research involves 72 students of X AP class in SMK Taruna Jaya Gresik as the sample. The instruments used in this study are questionnaire, documentation, and observation. The result shows the correlation between the facilities variable and the students achievement, it is shown by  tcount = 4,125 >ttable = 1,666. While the correlation between the study method variable and the students achievement shown by  tcount = 4,601 >ttable  = 1,666. In other words, there is a positive effect between the facilities variable and the study method to the students achievement hich is shown by = 55,039>  = 3,974.